The effect of customer-brand relationship investments on customer engagement: an imperative for sustained competitiveness - Zuraidah Zainol; Norjaya Mohd. Yasin; Nor Asiah Omar; Nik M. Hazrul Nik Hashim; Juliana Osman (Penerbit Universiti Kebangsaan Malaysia, 2015)
Using the extended Resource Investment Model, this study investigated the effect of customerbrand investments in building a strong customer engagement. Data were collected from a sample of 200 mobile phone customers using self-administered questionnaire, and analyzed through the utilization of multiple linear regressions analysis. The findings revealed that investments in customer and brand relationship significantly induce the customer to be engaged to a brand. Besides, the findings indicated that customer investment partially mediates the relationship between perceived brand investment and customer engagement. This study is one of the first to test the applicability of resource investment model in the context of customer-brand relationship. It concentrated on customers’ perception of their relationships with mobile phone brand in the Malaysia’s context. Accordingly, this study provides useful insight for companies in developing a strong customer-brand relationship; and consequently to sustain their competitiveness.